564. Higher "No Show" Rates Are Associated with Lower Rates of Retention in HIV Care and Viral Suppression. (26th November 2018) - Althoff, Amy; Dwyer, Madeline; Chew, Valeria; Gracely, Edward
Abstract: Background: Retention in HIV care has become the keystone of effective HIV treatment, but with less than 50% of people living with HIV/AIDS (PLWHA) engaged in care, a demand exists to better address patients' needs and to decrease viral transmission. While we know that missed visits can lead to poor outcomes, the science behind "no show" events, and the relationship of "no shows" to patients falling out of care has not been defined. Methods: We performed a chart review of 1, 179 patients from DUCOM's HIV clinic, the Partnership Comprehensive Care Practice, and examined medical appointment outcomes between July, 2013 and December, 2014. "No show" was defined as a visit not attended, cancelled or rescheduled. An attended visit between January and July 2015 defined a patient as retained. Our aims were to evaluate "no show" events, characterize those who "no show, " and determine predictors of (i) No Show rate (NSR ), (ii) Retention (including NSR as a predictor ), and (iii) Viral suppression (VS) (including NSR and Retention as predictors ). We queried three databases Allscripts, Careware, and RedCap, used SPSS for data analysis, and performed multiple linear and logistic regression to assess relationships between potential covariates and the three outcomes. Results: 80% of patients "no showed" at least once, and 23% of all appointments resulted in "no shows." Nine hundred and forty-one patients (80%) were retained. 85% of all patients were virally suppressed. Gender, zip code, and housing status were not associated with any of the three outcomes. Being older ( P < 0.001), white race ( P = 0.001), and private insurance ( P = 0.014) were associated with lower NSR, while substance use ( P < 0.001) and mental illness ( P = 0.038) were associated with a higher NSR. Among other findings, more years positive was associated with greater retention ( P = 0.003), and notably, a higher NSR was a strong and significant predictor of not being retained in care ( P < 0.001). In multivariate analysis, only NSR ( P < 0.001) and retention in care ( P = 0.037) predicted VS. Conclusion: PLWHA who "no show" are at a higher risk of viral nonsuppression and of falling out of care than those who attend their appointments even after adjusting for confounding variables. Interventions to address "no shows" in a timely manner and identify barriers must be developed in order to prevent patients from falling out of care. Disclosures: All authors: No reported disclosures.